Technical Efficiency Of Smallholders Of Oil Palm Cultivation In Ogan Komering Ilir - Armina Fariani; Jamhari Jamhari; Any Suryantini (Agro Ekonomi, 2018)
This study aims to (1) identify the factors affecting the production of oil palm cultivation business by the smallholders and (2) identify the technical level as well as factors influencing business inefficiency of oil palm cultivation by the smallholders  in Air Sugihan Sub District of Ogan Komering Ilir Regency, South Sumatera Province.  This research uses the  basic method of analytical descriptive method.  The data were collected by way of observation and direct interviews in the field guided by a questionnaire.  The research location was determined purposively, that is in Pangkalan Damai Village, Air Sugihan Sub-district, Ogan Komering Ilir Municipality, South Sumatera Province. Sampling was conducted using non probabilistic sampling method (purposive sampling).  The research investigated 79 smallholder farmers of oil palm cultivation in Pangkalan Damai village of Air Sugihan Sub-district, Ogan Komering Ilir Municipality, South Sumatera Province.  On the basis of the analysis, it is revealed  that (1) the factors affecting the increase of palm production were labor, land area, TSP fertilizer, NPK fertilizer, organic fertilizer, herbicides and insecticides which also have an effect on decreasing  palm production. (2) Palm plantation business was technically efficient with the average technical level of smallholder palm farmers in Air Sugihan Sub-district of Ogan Komering Ilir Municipality of 0.86090.  Factors that decrease the technical inefficiency in smallholder palm cultivation in Air Sugihan Sub-district of Ogan Komering Ilir Regency were farmers’ education level.  This information can be used by the goverment to improve technical efficiency through education in the form of counseling and training to increase production.